An assessment of the effectiveness of southern African development community (SADC) in resolving the Zimbabwe crisis from 2000-2016 - James, Tholakele (Midlands State University, 2018)
Zimbabwe after independence was hailed as the breadbasket of the Southern African region. Today the country has become dependent on other states in the Southern region and beyond Africa. Zimbabwe from the period of 2000, faced a multidimensional crisis which negatively impacted on the Zimbabwean population leading to many people migrating to neighboring states in search for greener pastures. The crisis in Zimbabwe also tremendously affected the southern region prompting SADC’s intervention. This study assesses the SADC’s efforts in resolving the political and economic crisis in Zimbabwe. It interrogates the methods or strategies which SADC used to resolve the Zimbabwean crisis, as they gave South Africa the mediating role between conflicting political parties. The study uses Transformative Mediation theory as an analytical framework. Transformative Mediation theory is based on empowering the disputing parties, and enhancing each party's recognition of the other. Empowerment and recognition are two key concepts of Transformative Mediation. These concepts are essential analytical tools in evaluating whether or not SADC’s mediation efforts succeeded in resolving the crisis.